Functional Lycopene Cyclase (CruA) in Cyanobacterium, Arthrospira platensis NIES-39, and its Role in Carotenoid Synthesis. (2nd March 2017) - Sugiyama, Kenjiro; Ebisawa, Masashi; Yamada, Masaharu; Nagashima, Yoshiki; Suzuki, Hideyuki; Maoka, Takashi; Takaichi, Shinichi
Abstract : The genus Arthrospira is filamentous, non-nitrogen-fixing cyanobacteria that is commercially important. We identified the molecular structures of carotenoids in Arthrospira platensis NIES-39. The major carotenoid identified was β-carotene. In addition, the hydroxyl derivatives of β-cryptoxanthin and (3 R, 3′ R )-zeaxanthin were also found to be present. The carotenoid glycosides were identified as (3 R, 2′ S )-myxol 2′-methylpentoside and oscillol 2, 2′-dimethylpentoside. The methylpentoside moiety was a mixture of fucoside and chinovoside in an approximate ratio of 1 : 4. Trace amounts of the ketocarotenoid 3′-hydroxyechinenone were also found. Three types of lycopene cyclases have been functionally confirmed in carotenogenesis organisms. In cyanobacteria, the functional lycopene cyclases (CrtL, CruA and CruP) have only been found in four species. In this study, we found that CruA exhibited lycopene cyclase activity in transformed Escherichia coli, which contains lycopene, but CruP exhibited no lycopene cyclase activity and crtL was absent. This is the third cyanobacterial species in which CruA activity has been confirmed. Neurosporene was not a substrate of CruA in E. coli, whereas lycopene cyclases of CrtY (bacteria), CrtL (plants) and CrtYB (fungi) have been reported to convert neurosporene to 7, 8-dihydro-β-carotene. β-Carotene hydroxylase (CrtR) was found to convert β-carotene to zeaxanthin in transformed E. coli, which contains β-carotene. Among the β-carotene hydroxylases, bacterial CrtZ and eukaryotic CrtR and BCH have similarities, whereas cyanobacterial CrtR appears to belong to another clade. Based on the identification of the carotenoids and the completion of the entire nucleotide sequence of the A. platensis NIES-39 genome, we propose a biosynthetic pathway for the carotenoids as well as the corresponding genes and enzymes.